Relaxin-2-secreting CAR-T cells exhibit enhanced efficacy in stromal-rich xenograft tumors - Ogawa, Hisataka; Ekawa, Tomoya; Mizote, Yu; Akazawa, Takashi; Tahara, Hideaki (Frontiers in Immunology, 2025)
IntroductionChimeric antigen receptor (CAR)-T cell therapy has demonstrated notable efficacy in treating hematological malignancies. Although it has shown promise in the clinical management of solid tumors, poor outcomes in clinical trials highlight the challenges in developing therapies suitable for the distinct tumor microenvironment, which features a dense stroma composed of fibroblasts and extracellular matrix proteins, such as collagen, hyaluronan, proteoglycans, laminin, and elastin. These predominantly fibroblast-produced components create a barrier that can impede CAR-T cell infiltration into tumors, limiting their efficacy. CAR-T cells that migrate from tumor vessels into the stroma may become trapped before reaching tumor cells.MethodsWe engineered CAR-T cells to secrete relaxin-2 (RLN2), an antifibrotic peptide hormone. Known for its role in pregnancy, RLN2 facilitates the softening and remodeling of collagen in the cervix and pelvic ligaments, and also promotes collagen degradation in the tumor microenvironment by upregulating matrix metalloproteinase levels by binding to the receptor LGR7/RXFP1.ResultsIn vitro studies revealed that cancer cells exposed to CAR-T cell-secreted RLN2 exhibited an increased expression and secretion of specific matrix metalloproteinases. In mouse xenograft models with abundant stromal content, RLN2-secreting CAR-T cells demonstrated significantly improved antitumor efficacy and infiltration into the tumor microenvironment compared to conventional CAR-T cells.DiscussionRLN2 may enhance the antitumor activity of CAR-T cells against solid tumors by promoting their infiltration into the tumor microenvironment.